Mucous Membrane Pemphigoid with Tracheal Involvement - Arash Minaie; Salim R. Surani (Case Reports in Pulmonology)
34-year-old African American female with history of pemphigoid presented with hemoptysis. Patient was found to have mucous membrane pemphigoid involving the oropharynx and extending to trachea, till just above main stem carina. Four other cases described mucosal pemphigoid involving the trachea. We hereby present a brief review of current consensus on management of mucous membrane pemphigoid with airway involvement.